Overcoming Linguacultural Barriers in Screen Translation: Cross-linguistic and Cross-cultural Encounters in the Italian Dubbed Version of Polyglot Films - Monti, Silvia (Journal of Audiovisual Translation, 2022)
The multilingual discourse practices distinctive of contemporary multicultural societies have assumed an increasingly prominent position in contemporary European and American multicultural films (cf. Bleichenbacher, 2008; Berghahn & Sternberg, 2010; Jacobsson, 2017), where code-switching (cf. Myers-Scotton, 1993; Auer, 1998; Gardner-Chloros, 2009; Bathia & Ritchie, 2014) stands out as a key conversational strategy when interethnic encounters are at stake. This ties issues of on-screen multilingualism to the field of audiovisual translation (cf. Corrius & Zabalbeascoa, 2011, 2019; Şerban, 2012; Zabalbeascoa & Voellmer, 2014; de Higes Andino, 2014), intended as a key vehicle of intercultural/interlinguistic mediation. This paper aims at looking contrastively and diachronically at how code-switching, implying the recurrent on-screen presence of L3s, has been dealt with in the original version and in the Italian dubbed versions of twenty European and American multicultural/multilingual films, belonging to different genres and released within a time span covering three decades, where interracial relationships are at centre stage; the main objective of this study is to verify whether specific translation, or non-translation, strategies are applied to the instances of language alternation either to faithfully re-create the original linguistic interplay for the Italian audience or to manipulate it in dubbing. Lay summary The multilingual discourse practices distinctive of contemporary multicultural societies have assumed an increasingly prominent position also in contemporary European and American multicultural films, where the alternation of different languages by bilingual/multilingual characters stands out as a key conversational strategy when interethnic encounters and cross-cultural romance are at stake. On-screen multilingualism thus results to be strictly tied to the field of audiovisual translation, nowadays intended as a crucial vehicle of intercultural/interlinguistic mediation worldwide. This paper aims at analyzing how different language alternation practices have been dealt with in the original version and in the Italian dubbed versions of twenty European and American multicultural/multilingual films, belonging to different genres and released within a time span of thirty years, where interracial relationships and love-stories are at centre stage. The main objective of this study is indeed to verify whether specific translation, or non-translation, strategies are applied to the instances of language alternation enacted throughout the film dialogues, either to faithfully re-create the original linguistic interplay for the Italian audience or to manipulate it through dubbing. All this primarily aims at pointing out what can be achieved by screen translation in terms of transcultural and translingual transmission, mediation and re-mediation when cross-cultural relations are at stake and at highlighting a series of translation (or non-translation) trends that increasingly favour affective bonds between Self and Other, liable to overcome cultural clashes as well as to cross linguistic bridges both on and off the screen.